A comparative study of the microtensile bond strength and microstructural differences between sclerotic and Normal dentine after surface pretreatment - Jinhua Wang; Weijian Song; Lei Zhu; Xin Wei (BMC, 2019)
Abstract Background The resin bond strength of sclerotic dentine is significantly lower than that of the normal dentine, which paused a challenge for bonding procedures clinically. The aim of this study was to compare the effects of different surface pretreatments on the micro-tensile bond strength and microstructure between sclerotic dentine and normal dentine. Methods Eighty teeth that were collected, forty premolars with typical wedge-shaped defects visually graded as class III were assigned as the sclerotic dentine group (SD), the other forty normal premolars with artificial wedge-shaped defects were assigned as the normal dentine group (ND). Each group was randomly subdivided into eight subgroups according to the solution used: 35% phosphoric acid, 15% EDTA, 5% or 10% NaClO. Then the dentine surface was examined using a scanning electron microscope (SEM). The lesions were restored using self-etching adhesive and the subsequent resin composite. The teeth were sectioned into sticks for the micro-tensile bond strength analysis, and the data were analysed using the SPSS17.0 software package (α = 0.05). Results First, for the ND groups, after pretreatment using 35% phosphoric acid, and 35% phosphoric acid + 5% or 10% sodium hypochlorite, the bonding strengths of the normal dentine were higher than that of the other groups (P < 0.05). Second, for the SD groups, after pretreatment using 35% phosphoric acid, 15% EDTA, and 35% phosphoric acid + 5% or 10% sodium hypochlorite, the bonding strengths of the sclerotic dentine were higher than that of the other groups (P < 0.05). Third, the bond strengths of the sclerotic dentine were lower than that of the normal dentine without any pretreatment (P < 0.05). After pretreatment using 35% phosphoric acid + 5% or 10% sodium hypochlorite, the bonding strengths of the sclerotic dentine were higher than that of the normal dentine (P < 0.05). SEM observation showed that the appearances of dentine surface were changed after pretreatment using the above solutions, with the reduced smear layer, opened small groove and increased dentinal tubules. Conclusion Pretreatment of dentine using 35% phosphoric acid+ 5% or + 10% sodium hypochlorite changed the microstructure of the sclerotic dentine surface and subsequently increased the micro-tensile bond strength.